Distorted Sandwich α‐Diimine PdII Catalyst: Linear Polyethylene and Synthesis of Ethylene/Acrylate Elastomers. Issue 45 (5th October 2021) - Liu, Yu‐Sheng; Harth, Eva
Abstract: The introduction of m ‐xylyl substituents to α‐diimine Pd II catalyst promotes living ethylene polymerization at room temperature and low pressure to yield high molecular weight polyethylene (PE) with low branching (<17/1000 C). m ‐Xylyl groups provide a highly effective blockage to the axial sites of the catalytic center and form a distorted sandwich geometry. The shielding prevents chain‐transfer and easy accessibility of polar monomers, leading to a living polymerization. Conducting a light irradiation as part of the one‐step metal‐organic insertion light initiated radical (MILRad) process leads to diblock copolymers of ethylene and acrylates. Incorporation of different acrylate block sequences can significantly modify the mechanical and chemical properties of block copolymers which can be modulated to be a hard plastic, elastomer, or semi‐amorphous polymer. Abstract : Distorted sandwich α‐diimine Pd II catalysts with m ‐xylyl groups for axial shielding of the metal center provide living polymerization of linear polyethylene with low branching to be turned into either hard plastics or thermoplastic elastomers incorporating a range of acrylates in a one‐pot by metal‐organic insertion light‐initiated polymerization.